17-AAG mediates targeting of HSP90 limits tert activity in peritoneal sarcoma related malignant ascites by downregulating cyclin D1 during cell cycle entry - Chaklader, M.; Das, P.; Pereira, J.A.; Law, A.; Chattopadhyay, S.; Chatterjee, R.; Mondal, A.; Law, S. (Experimental Oncology, 2012)
Aim: Peritoneal or retro-peritoneal sarcomatosis related malignant ascites formation is a rare but serious consequence of the locoregional metastatic event. The present work aimed to study the effect of the Hsp90 inhibitor (17-AAG), an ansamycin analog, on cell cycle and DNA replication specific chaperone-clients interaction in the event of peritoneal sarcoma related malignant ascites formation in mouse model at the late stage of malignant growth. Methods: We administered 17-AAG, an Hsp90 inhibitor, divided doses (330 μg/kg b.w./day for first five days then next ten days with166 μg/kg b.w./day) through intra-peritoneal route of inbred Swiss albino mice bearing full grown peritoneal malignant ascites of sarcoma-180. Our study was evaluated by peripheral blood hemogram analysis, malignant ascitic cytology, cell viability test, survival time and mitotic indexing. Furthermore, flowcytometric HSP90, TERT, CyclinD1, PCNA and GM-CSF expression analysis has been considered for special objective of the study. Results: Our experimental efforts reduced the aggressive proliferation of malignant ascites by drastic downregulation of TERT and cyclin D1 on the verge of cell cycle entry along with DNA replication processivity factor PCNA by directly modulating their folding machinery — heat shock protein 90. Consequently, we observed that malignant ascitic cells became error prone during the event of karyokinesis and produced micronucleus containing malignant cells with low viability. Peripheral neutrophilia due to over-expression of GM-CSF by the peritoneal malignant ascites were also controlled by the treatment with 17-AAG and overall, the treatment modality improved the median survival time. Conclusion: Finally we can conclude that 17AAG administration might serve as a prospective pharmacological agent for the management of peritoneal sarcoma related malignant ascites and throws light towards prolonged survival of the patients concerned.